The promotion effects of silicate mineral maifanite on the growth of submerged macrophytes Hydrilla verticillata. (December 2020) - Liu, Yunli; Han, Fan; Bai, Guoliang; Kong, Lingwei; Liu, Zisen; Wang, Chuan; Liu, Biyun; He, Feng; Wu, Zhenbin; Zhang, Yi
Abstract: The effects of maifanite on the physiological and phytochemical process of submerged macrophytes Hydrilla verticillate ( H.verticillata ) were investigated for the first time in the study. The growth index: plant biomass, root length, plant height and leaf spacing, and physiological and phytochemical indexes: chlorophyll, soluble protein, malondialdehyde (MDA), peroxidase (POD), superoxide dismutase (SOD) content and vitality of the roots of H.verticillata were tested. The results found that maifanite can significantly promote the growth of H.verticillata . The modified maifanite were more conducive to plant growth compared with the raw maifanite, and the MM1 group had the best growth promoting effect. The physiological and phytochemical indexes showed that maifanite can delay the aging process of H.verticillata (P < 0.05). The possible reasons for promoting H.verticillata growth were that maifanite can provide excellent propagation conditions for plant rhizosphere microorganisms, contains abundant major and microelements, and improve the sediment microenvironment. This study may provide a technique for the further application of maifanite in the field of ecological restoration. Graphical abstract: Image 1 Highlights: Maifanite could significantly promote the growth of H.verticillata. Maifanite can delay the aging process of H.verticillata. The diversity and richness of microbial communities in maifanite group were more. Maifanite can dissolve trace elements and improve the sediment microenvironment. Maifanite can be applied to ecological restoration projects in eutrophic lakes. Abstract : Maifanite can significantly promote the growth of H.verticillata . The physiological and phytochemical indexes showed that maifanite can delay the aging process of H.verticillata.